Cases in Government Succession Planning action-oriented strategies for public-sector human capital management, workforce planning, succession planning, and talent management - Rothwell William J. (Amherst HRD Press, 2008)
Cases in Government Succession Planning is designed for government leaders, government human resource professionals, and students interested in government careers. In four sections, the book examines government succession planning, human capital management, workforce planning, and talent management. Part 1 presents five cases from international settings. Part 11 focuses on the federal government of the United States and includes seven cases. Part 111 centers on state government agencies in the United States and presents five case studies. Part IV explores succession practices in local governments of the United States. In addition, a CD-ROM provides you with many resources on succession planning from case authors and public sources. You will learn: The differences in the way public-sector and private-sector entities set up and describe their programs How models should guide action and on what basis should a program be designed and carried out Pitfalls to be avoided Lessons learned and how to apply them to your unique agency setting.
Accompanied by 1 CD-ROM containing additional resources ; contents of CD-ROM listed on p. 295-297. Includes bibliographical references (p. 299-300).
Keywords: Civil service, State governments Local Government Personnel management Human capital-Planning Manpower planning Strategic Planning